Determinates of Islamic banks liquidity. Issue 8 (21st February 2020) - Al-Harbi, Ahmad
Abstract : Purpose: The purpose of this paper is to investigate the determinants of Islam banks (IBs) liquidity. Design/methodology/approach: In this paper, the author uses a generalized least square fixed effect model on an unbalanced panel data set of all IBs operating in the Organization of Islamic Cooperation countries over the period 1989-2008. Findings: The estimation results show that all the determinants have statistically significant relationships with IBs' liquidity but with different signs. On the one hand, foreign ownership, credit risk, profitability, inflation rate, monetary policy and deposit insurance negatively affected IBs liquidity. On the other hand, capital ratio, size gross domestic product growth and concentration have a positive nexus with IBs' liquidity. Originality/value: According to the best of the author's knowledge, this is the first empirical study to investigate the determinants of IBs liquidity using cross-country data with a large sample of IBs (110 banks) and over a long period (19 years). Also, the paper included variables that had not been discussed on the previous studies, which used cross-country data, such as efficiency, deposit insurance, monetary policy, concentration and market capitalization.